Improving hole mobility with the heterojunction of graphitic carbon nitride and titanium dioxide via soft template process in photoelectrocatalytic water splitting. (29th November 2019) - Murugan, C.; Bhojanaa, K.B.; Ong, Wee-Jun; Jothivenkatachalam, K.; Pandikumar, A.
Abstract: In this current work, we have prepared graphitic carbon nitride@titanium dioxide (g-C₃N₄@TiO2 ) nanocomposite material via simple one-step soft template synthesis to improve the efficacy of charge separation in photoelectrocatalytic water splitting. The g-C3 N4, a photoactive component was incorporated in varying amounts into TiO2, and the resulting composites were confirmed to have improved photoelectrocatalytic activity over the bare-TiO2 . Under the optimal experimental condition, the 20 wt % g-C₃N₄@TiO2 composite exhibited the highest photoelectrocatalytic activity. The g-C3 N4 has an ability to absorb the incident photons, resulting in excitation of electrons between the frontier orbitals. These excited electrons move to TiO2 via the interfacial border, hindering the recombination of the photo-induced electrons and holes and thus, improves the overall performance of the photocatalyst. The improved photoelectrocatalytic performance by g-C3 N4 @TiO2 was ascribed to the overall impact of g-C3 N4 that increased its absorptive spectrum into the visible region. As such, the presence of heterojunction in the prepared composite not only aided the separation of the photogenerated charge carriers but also maintained its strong oxidation and reduction capability in the photoelectrocatalytic water splitting. Graphical abstract: Image 1 Highlights: g-C3 N4 @TiO2 nanocomposite synthesized via simple one-step soft template method. g-C3 N4 effectively extend the absorption of TiO2 to visible light range. 20 wt% g-C3 N4 @TiO2 showed ∼1.4 & 595-fold higher efficiency than TiO2 and g-C3 N4 . Formation of heterojunction between g-C3 N4 and TiO2 . Minimized charge recombination & improved interfacial charge transfer.